Optimisation of IT teaching materials for students of humanities and social sciences - Kovács, Edina (Tudásmenedzsment, 2022)
The demands of the 21st century mean that without digital competence and basic IT skills we cannot thrive in society. This is particularly true for students leaving higher education. Today, it is not only students in engineering and science who need to acquire ICT and IT skills. Although the latest version of the National Curriculum sets the development of digital competences as a task, the previous curriculum did not require students leaving public education to have these competences. For this reason, it is particularly important in higher education in the humanities and social sciences to develop digital competences in addition to IT skills. The paper presents the history of the introduction of IT and computing in higher education, and the process of how these subjects have been replaced in the humanities as well as in technical higher education because of the Bologna process. In addition, it presents the elements of the implementation of an IT course in an LMS system. It presents good practices and tools to increase not only students' knowledge but also their motivation, digital competences and interest in IT content.